Предмет: Математика,
автор: mixanik148
Прoдифференцировать функцию
f (x) = (2x – 3)^√3 +(√3) ^2x-3
Ответы
Автор ответа:
0
Ответ:
f' (x) =2√3 * (2x – 3)^(√3 - 1) +2ln(√3) * (√3) ^2x
Пошаговое объяснение:
f (x) = (2x – 3)^√3 +(√3) ^2x-3
f' (x) =√3 * (2x – 3)^(√3 - 1)*2 +(√3) ^2x*ln(√3)*2-0
f' (x) =2√3 * (2x – 3)^(√3 - 1) +2ln(√3) * (√3) ^2x
Похожие вопросы
Предмет: Английский язык,
автор: 49601
Предмет: Русский язык,
автор: viktoriyaparfenova
Предмет: Русский язык,
автор: ВсеЗнайка2017
Предмет: Алгебра,
автор: радость19
Предмет: География,
автор: kiril04kos5ar